Engineering for Rural Development 2019
DOI: 10.22616/erdev2019.18.n074
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of winter triticale grain depending on type of tillage in crop rotation

Abstract: Triticale is a fodder cereal with a high nutritional value of grains. It can also be used for food purposes, so the chemical composition of the grain is important. The aim of the study was to determine the changes in the macroelement content in the grains of winter triticale cultivars under the use of different tillage methods and the percentage of cereals in the crop rotation. The research shows that the chemical composition of grains depends on the weather conditions, tillage method, and the share of cereals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[47]. However, the amino acid profile of triticale flour in published studies [48][49][50][51][52] did not display separately the amounts of Asp/Asn and Glu/Gln, because the analytical methods used did not allow distinguishing carboxylated and amide forms of these amino acids. In the recent studies [17,53], data for free Asn content in triticale varieties have been published, but no information on a full amino acid profile.…”
Section: Amino Acid Profiles Of Cereal Floursmentioning
confidence: 98%
“…[47]. However, the amino acid profile of triticale flour in published studies [48][49][50][51][52] did not display separately the amounts of Asp/Asn and Glu/Gln, because the analytical methods used did not allow distinguishing carboxylated and amide forms of these amino acids. In the recent studies [17,53], data for free Asn content in triticale varieties have been published, but no information on a full amino acid profile.…”
Section: Amino Acid Profiles Of Cereal Floursmentioning
confidence: 98%
“…18 Another study in Poland showed that the reduced tillage decreased minerals such as K, Ca and Na compared with CT for triticale grain. 19 Regarding bioactive compounds in the maize grains, three tillage systems gave different results: NT had the highest phenol content, CT had the highest carotenoid content and tocopherol was higher under reduced tillage. 20 Djouadi et al 21 explained that the non-significant effect of NT on durum wheat in Algeria could be due to the short-term adoption of NT without soil cover.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments conducted for 3 years in Poland on two barley grains showed that reduced tillage increased macro‐minerals (P and K) and decreased micro‐minerals (Fe, Zn and Cu) compared to the CT system 18 . Another study in Poland showed that the reduced tillage decreased minerals such as K, Ca and Na compared with CT for triticale grain 19 . Regarding bioactive compounds in the maize grains, three tillage systems gave different results: NT had the highest phenol content, CT had the highest carotenoid content and tocopherol was higher under reduced tillage 20 …”
Section: Introductionmentioning
confidence: 99%
“…This cereal species is becoming more and more popular among farmers, also with those operating in the organic system. This is due to its beneficial traits, such as relatively low soil requirements [7,8], a higher resistance to diseases and soil acidification than wheat [6], significant yield potential [9][10][11][12], high fodder value [7,[13][14][15][16][17], and resistance to abiotic stresses, such as drought and frost [1,12,18]. Winter triticale is more sensitive to a forecrop than rye, but less sensitive than wheat and it can be cultivated after other cereals as it responds with a relatively small reduction of yield to a less favorable forecrop [19].…”
Section: Introductionmentioning
confidence: 99%